2023
DOI: 10.3389/fmed.2023.1268220
|View full text |Cite
|
Sign up to set email alerts
|

Should acupuncture become a complementary therapy in the treatment of uterine fibroid: a systematic review and meta-analysis of randomized controlled trials

Yuehan Ren,
Junning Zhang,
Weizhen Wu
et al.

Abstract: BackgroundUterine fibroids (UFs) are the most common benign tumors in women of reproductive age. The most effective treatment is myomectomy, but there is no long-term or low-invasive treatment option exists. Acupuncture can be used to treat UFs in a variety of ways. However, there is no meta-analytic synthesis including valid data that explored the efficacy of acupuncture for UFs.ObjectiveTo assess the efficacy and safety of acupuncture for treating UFs.MethodsThe PRISMA 2020 checklist was used. We identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
(48 reference statements)
0
1
0
Order By: Relevance
“…Other studies have reported that cervical Jiaji acupuncture combined with the Fengchi, Hou Xi, and Shu gu points can relieve the symptoms of patients with vertigo, and these mechanisms may be related to the acceleration of the blood flow of the vertebrobasilar artery[ 6 ]. Previous studies used "regulating spleen and stomach" acupuncture combined with Fengchi acupoint acupuncture to treat cervical vertigo, and the improved effect on the basilar artery and vertebral artery blood flow was confirmed[ 7 ]. Combined with the above results, it can be determined that acupuncture at the Fengchi point can improve the blood flow and circulation of the vertebrobasilar artery, which is beneficial for improving the state of ischemia and hypoxia in the inner ear.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies have reported that cervical Jiaji acupuncture combined with the Fengchi, Hou Xi, and Shu gu points can relieve the symptoms of patients with vertigo, and these mechanisms may be related to the acceleration of the blood flow of the vertebrobasilar artery[ 6 ]. Previous studies used "regulating spleen and stomach" acupuncture combined with Fengchi acupoint acupuncture to treat cervical vertigo, and the improved effect on the basilar artery and vertebral artery blood flow was confirmed[ 7 ]. Combined with the above results, it can be determined that acupuncture at the Fengchi point can improve the blood flow and circulation of the vertebrobasilar artery, which is beneficial for improving the state of ischemia and hypoxia in the inner ear.…”
Section: Resultsmentioning
confidence: 99%